Challenges faced by upper indus basin (UIB) communities due to climate change - Rudraakshi Tiwari; Prof. (Dr.) Indrani Chakravorty; Prof. (Dr.) Subhrajit Banerjee (International Journal of Environmental Planning and Development Architecture, 2024)
The Upper Indus Basin (UIB) communities are heavily dependent on water resources for their sustenance. The region relies on glacial and snowmelts for irrigation water, energy, domestic and irrigation uses. Climate change poses threat to vulnerable region all around the world, and Upper Indus Basin (UIB) is no different. The variability in climatic conditions such change in precipitation pattern and temperature fluctuations have disrupted the agriculture practices of the region and threatened food security and livelihoods of the people living in the basin. The transboundary region of Upper Indus Basin is constantly under tension due to geopolitics of the countries involved and the consequence of climate change tend to add to the challenges faced by people living in this region. The research aims to understand effect of climate change on the complex hydrological regime of the basin and its consequence on the communities living there. Furthermore, it intends to explore nexus of climate change with broader socio-economic trends such as demographics, land use patterns and economic activities. The study delves into the implications of changed hydrology and glacial system on agriculture and pastureland productivity. The research also helps in understanding the heightened vulnerability of UIB communities due to increased susceptibility of natural calamities like glacial lake outburst floods (GLOFs) and flash floods. The study seeks to contribute valuable insights to the global discussion on climate change impacts, drawing attention to the need for targeted intervention to protect the wellbeing of Upper Indus Basin (UIB) communities and guarantee the sustainability of this critical watershed region.
Keywords: Climate change; Food insecurity; Upper Indus Basin; hydrological regime; pastureland depletion